A new species of the montane lacewing genus Rapisma McLachlan (Neuroptera, Ithonidae) from China - Liu, Xingyue; Li, Di; Yang, Zizhong (Zootaxa, 2018)
The genus Rapisma McLachlan, 1866 (Insecta: Neuroptera: Ithonidae) is a rare and poorly known lacewing group endemic to Asia. Previously, there were five species recorded from China. Here we describe a new species of Rapisma from Mt. Gaoligongshan, southwestern Yunnan, China, namely Rapisma gaoligongensis sp. nov. The new species appears to be closely related to Rapisma corundum Barnard, 1981 from eastern Myanmar and Rapisma daianum Yang, 1993 from southern Yunnan, China, and it belongs to a group of Rapisma species with pectinate male antennae and posteriorly bilobed male gonocoxites 9.